2015
DOI: 10.1002/jcb.25196
|View full text |Cite
|
Sign up to set email alerts
|

Notch‐1 Promotes Stemness and Epithelial to Mesenchymal Transition in Colorectal Cancer

Abstract: Colorectal cancer (CRC) is the third leading cause of cancer death in the United States, resulting in an average of 50,000 deaths per year. Surgery and combination chemotherapy comprise current treatment strategies. However, curative options are limited if surgery and chemotherapy are unsuccessful. Several studies have indicated that CRC aggressiveness and potential for metastatic spread are associated with the acquisition of stem cell like properties. The Notch-1 receptor and its cognate signaling pathway is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
85
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(95 citation statements)
references
References 32 publications
4
85
1
1
Order By: Relevance
“…42 Strikingly, Notch was found to promote stemness and EMT in colorectal cancer. 43 Similarly, Notch signaling triggered EMT, leading to enhanced invasion and metastasis in adenoid cystic carcinoma. 44 One study showed that aberrant expression of EMT markers E-cadherin, Vimentin, and Notch-1 was observed in prostate cancer specimen and bone metastasis tissues, suggesting that Nocth-1 could play a role in bone metastasis via regulation of EMT.…”
Section: Discussionmentioning
confidence: 99%
“…42 Strikingly, Notch was found to promote stemness and EMT in colorectal cancer. 43 Similarly, Notch signaling triggered EMT, leading to enhanced invasion and metastasis in adenoid cystic carcinoma. 44 One study showed that aberrant expression of EMT markers E-cadherin, Vimentin, and Notch-1 was observed in prostate cancer specimen and bone metastasis tissues, suggesting that Nocth-1 could play a role in bone metastasis via regulation of EMT.…”
Section: Discussionmentioning
confidence: 99%
“…EMT has been mechanistically linked to stem-like signatures regulated by Notch-1 in prostate cancer cells [48]. In colorectal cancer patient specimens, Notch-1 was found to be up-regulated in colon tumor tissue and to increase the abundance of EMT- and stemness-associated proteins, such as CD44, Slug and Smad-3 [49]. These studies indicated that the Notch pathway was associated with the EMT and acquisition of stem cell-like properties in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Up-regulation of NOTCH1, JAG ligands and HES1 in CRC cell lines results in the increased expression of the EMT/stemness-associated proteins: CD44, SLUG, and SMAD3 (7,8). High expression of HES1 is significantly correlated with distal metastasis at diagnosis, and unfavorable prognostic outcome for CRC patients (9).…”
Section: Introductionmentioning
confidence: 99%